POST-HARVEST HANDLING EVALUATION OF RED CHILI ALONG THE SUPPLY CHAIN IN SUKABUMI - Laras Putri Wigati; Sutrisno Suro Mardjan; Emmy Darmawati (AGROINTEK, 2020)
Red chili is a horticultural product commonly used by people in their daily lives. Horticulture products have a long handling process until they reach consumers. The postharvest handling generally must be carried out are collecting, sorting, grading, packaging, transporting, distributing. This study was conducted to analyze the suitability of postharvest handling from each actor in the supply chain according to the standard operational procedure (SOP) of postharvest handling in red chili. This study used purposive and snowball sampling as the methods of selecting respondents. The percentage of the suitability of postharvest toward SOP was obtained with a simple data calculation. This study found that the supply chain of red chili in the Perbawati village of Sukabumi has two types of chains. Postharvest handling of red chili had done were sorting and packaging while another postharvest handling such as collecting, grading, cleaning had not done by the farmers. For the farmers and middleman handling practices compare to the standard operational procedure of postharvest red chili, was 45.56% of post-harvest handling that suitable with the SOP.